2023
DOI: 10.3390/polym15020390
|View full text |Cite
|
Sign up to set email alerts
|

Fused Deposition Modeling and Characterization of Heat Shape Memory Poly(lactic) Acid-Based Porous Vascular Scaffold

Abstract: Shape memory polymers have received widespread attention from researchers because of their low density, shape variety, responsiveness to the environment, and transparency. This study deals with heat-shape memory polymers (SMPs) based on polylactic acid (PLA) for designing and fabricating a novel porous vascular scaffold to treat vascular restenosis. The solid isotropic material penalization method (SIMP) was applied to optimize the vascular scaffolds. Based on the torsional torque loading of Hyperworks Optistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Reproduced under the term of CC‐BY license. [ 123 ] Copyright 2023, The Authors, published by MDPI. e) PLA‐based gripper made of the bioinspired pattern.…”
Section: D/4d Printing Of the Biodegradable Soft Sensors And Actuatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reproduced under the term of CC‐BY license. [ 123 ] Copyright 2023, The Authors, published by MDPI. e) PLA‐based gripper made of the bioinspired pattern.…”
Section: D/4d Printing Of the Biodegradable Soft Sensors And Actuatorsmentioning
confidence: 99%
“…The researchers used 4D printing to prepare stents with different unit cells and investigated the effect of the helical angle on the shrinkage ratios of the stents. Zhang et al [ 123 ] reported the use of SMPs based on PLA for designing and fabricating a novel porous vascular scaffold to treat vascular restenosis employing the FFF method (Figure 5d). The SMPs were characterized for their thermal, mechanical, and shape memory properties, and it was found that they could be perfectly adaptable in fabricating the vascular scaffold for vascular implantation.…”
Section: D/4d Printing Of the Biodegradable Soft Sensors And Actuatorsmentioning
confidence: 99%
See 3 more Smart Citations